A survey of Australian and New Zealand medical parents' experiences of infertility, pregnancy, and parenthood - Kevric, Jasmina; Suter, Katherine; Hodgson, Russell; Chew, Grace (Frontiers in Medicine, 2022)
OBJECTIVE To describe the incidence of infertility, pregnancy complications and breastfeeding practices among Australian and New Zealand doctors and identify factors associated with increased pregnancy complication rates. METHODS A survey ANZ doctors using an online questionnaire during November 2021. RESULTS 1099 responses were received. The median age of female doctors at the time of their first child was 32.4. Fertility testing was undertaken by 37%, with 27% having in vitro fertilisation. More than 60% of respondents delayed family planning due to work. Pregnancy loss occurred in 36% of respondents, and 50% suffered a pregnancy complication. There were significant differences between specialists, with surgeons working longer hours before and after pregnancy, but having greater access to maternity leave than general practitioners. CONCLUSION Female doctors delay starting and completing their family due to work-related demands and structural biases in career progression, which may result in higher infertility and pregnancy complication rates.